The Influence of Organization and Interpretation on the Performance of the North Sumatra Province Revenue Service - M. Ismail P. Sinaga (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Influence of Organization and Interpretation on the Performance of the Regional Revenue Service of North Sumatra Province. The purpose of this study was to analyze the effect of Organizational activities on the Performance Improvement of Regional Original Income in the Province of North Sumatra and to analyze the effect of Interpretation on the Improvement of the Performance of Regional Original Income in the Province of North Sumatra. The data used are primary data and secondary data. The data analysis method used is correlation analysis, determination analysis, and multiple linear regression analysis. The samples taken in this study were 166 employees of the North Sumatra Province Revenue Service. The results of the study indicate that there is a significant influence of the Organization on the Performance of the Revenue Service in North Sumatra Province which can determine the direction or planning for the achievement of the vision and mission, improve management in order to increase PAD, motivate, inspire, support ANS in carrying out its work and manage relationships with stakeholders. And furthermore, there is a significant effect of Interpretation on the Performance of the Revenue Service in North Sumatra Province, in this case it can provide information related to local taxes, current and future regional levies, activities to increase PAD by taking into account the needs of stakeholders, availability of resources. resources as well as modernization and innovation in the use of technology in the PAD program.